Kontribusi Pemikiran John Dewey mengenai Pembelajaran Berbasis Pengalaman bagi Pendidikan Kristen Masa Kini - Pasang, Agustina (PEADA': Jurnal Pendidikan Kristen, 2024)
This article aims to find the contribution of John Dewey’s thoughts on experiential learning for Christian education today. This study uses qualitative research with a content analysis method approach. Based on this method, it is found that the contribution of John Dewey’s thoughts on experiential learning for Christian education is learning that places the experience of students as the focus of learning both in theory and practice or direct experience that can be applied through social activities and service to the community so that understanding of religious values is reflected in real life where the intended experience is personal experience that they not only learn the concept of material or theory but at the same time become experience, but does not mean this learning only emphasizes the cognitive aspect because it still involves the affective and psychomotor aspects of student. Also provides wider opportunities for students to interact with each other and with teachers/educators and the environment.